Investigation of TNFR2 expressing t regulatory cells and inflammatory mediators in chronic rhinosinusitis with nasal polyps’ patients attending Hospital Universiti Sains Malaysia - Yusoff, Nur Najwa Farahin M (2024)
Chronic Rhinosinusitis with Nasal Polyps (CRSwNP) is an inflammatory disease of the paranasal sinus mucosa predominantly driven by chronic type 2 inflammation. CRSwNP pathophysiology is believed to result from immune dysregulation with insufficient regulatory cells to sustain immunological homeostasis. Regulatory T cells (Tregs) are critical regulators of immune tolerance. Tregs expressing tumor necrosis factor receptor 2 (TNFR2) have been recently characterized as the most potently suppressive Tregs population. This study aimed to determine the proportion of TNFR2+ Tregs subsets in Peripheral Blood Mononuclear Cells (PBMC) of the CRSwNP patients compared to healthy controls. The secretion levels of cytokines; IL-4, IL-10 and TNF were accessed to support the findings on TNFR2+ Treg cells. Twenty-five CRSwNP patients (n = 25) and twenty-five healthy controls (n = 25) were recruited in this study. A five-color flow cytometer was used to determine the proportion of the expression of Tregs subsets. PBMC was isolated from peripheral blood using Lymphoprep gradient centrifugation and stained with fluorophore-labelled antibodies. Tregs subsets were identified using markers of CD4, CD25, CD127, TNFR2 and Foxp3, in one antibody cocktail. The cytokines from the serum were measured using Legend Plex ® cytometric-based immunoassays. The result showed CRSwNP patients exhibited a significant upregulation of TNFR2 proportion in both phenotype of CD4+Foxp3+ T cells (p < 0.05) and CD4+CD25+CD127-Foxp3+ T cells compared to healthy individuals, (p<0.05). Similarly, TNFR2 also showed a significantly higher expression in Tregs than Tconvs in both patients and healthy individuals, indicating TNFR2 was preferentially expressed on Tregs over Tconvs, p < 0.001. In addition, significant increase of TNF level also observed in CRSwNP patients compared to healthy individuals, (p < 0.001). However, no correlation was found between the clinicocharacteristics of CRSwNP patients and TNFR2+ Tregs subsets. In conclusion, this study suggested the up regulation of TNFR2+ Tregs as the most potent suppressive subset and high level of TNF, prone to indicate a functioning immune suppression to establish immune tolerance in treated CRSwNP patients, partly via TNF-TNFR2 axis.